Vulval leiomyoma: a rare clinical entity - P., Amudha; E., Kalarani; A., Karthika Devi; M., Swathi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Vulval leiomyomas are rare benign tumors which arise from the smooth muscle cells within erectile tissue, blood vessel walls or round ligament remnants in labium majus. As they are rare, clinical diagnosis is often challenging. We report a case of 64 year old postmenopausal woman with a labial swelling of 3 months duration. It was clinically diagnosed as Bartholin`s gland cyst and intraoperatively the gross appearance was that of a leiomyoma and surgical excision was performed. Histopathological analysis confirmed the diagnosis of leiomyoma.